Historiology; From Reconstruction to Deconstruction: A Critique on the Book Deconstruction of History - Sayyed Abolfazl Razavi (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
Manzello’s encounter with the nature of historical cognition and the quality of its achievement on the two epistemological horizons of modernism and postmodernism in the light of the three historical approaches of reconstructionism, constructivism, and deconstructionism in the transition from modernism to postmodernism, with the subtle difference between the two concepts of "historian" and the “history-researcher” is considered to be examined. The historian who lives in the discourse space of the realization of the historical subject, immersed in modern conditions, experiences and compels the resulting comprehension of history and creates historical documents. The “history-researcher” lives in the contemporary discourse space and thinks in accordance with the structural and discourse requirements of his time and communicates with history. The history-researcher, both in the sense of reconstruction-construction and in the sense of deconstruction, presents his narrative in the light of narration and passing through events. A detailed description of the above-mentioned three approaches is considered in Manzello's book entitled “Deconstruction of History”, which is examined in both negative and positive aspects.